2019
DOI: 10.1634/theoncologist.2019-0406
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Polypharmacy and Inappropriate Medications with Adverse Outcomes in Older Adults with Cancer: A Systematic Review and Meta-Analysis

Abstract: Background Polypharmacy (PP) and potentially inappropriate medications (PIM) are highly prevalent in older adults with cancer. This study systematically reviews the associations of PP and/or PIM with outcomes and, through a meta‐analysis, obtains estimates of postoperative outcomes associated with PP in this population. Materials and Methods We searched PubMed, Embase, Web of Science, and Cochrane Register of Clinical Trials using standardized terms for concepts of PP, PIM, and cancer. Eligible studies include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 80 publications
(147 reference statements)
5
77
1
3
Order By: Relevance
“…More than 90% of older adults (≥65 years) regularly take at least one medication, and 57% of older women and 44% of older men report using 5 or more medications weekly (i.e., polypharmacy) [ 194 ]. Polypharmacy and the use of inappropriate medications in older individuals is independently associated with functional impairment [ 195 ] and a decline in activities of daily living [ 196 ] that may me mediated, at least in part, through drug-microbiome relationships. Medications and the microbiome have bidirectional interactions; medications may elicit inhibitory or beneficial effects on gut microbes, meanwhile, gut microbes play an active role in drug metabolism [ 197 ].…”
Section: Lifestyle Factors Contributing To Age-related Microbiome mentioning
confidence: 99%
“…More than 90% of older adults (≥65 years) regularly take at least one medication, and 57% of older women and 44% of older men report using 5 or more medications weekly (i.e., polypharmacy) [ 194 ]. Polypharmacy and the use of inappropriate medications in older individuals is independently associated with functional impairment [ 195 ] and a decline in activities of daily living [ 196 ] that may me mediated, at least in part, through drug-microbiome relationships. Medications and the microbiome have bidirectional interactions; medications may elicit inhibitory or beneficial effects on gut microbes, meanwhile, gut microbes play an active role in drug metabolism [ 197 ].…”
Section: Lifestyle Factors Contributing To Age-related Microbiome mentioning
confidence: 99%
“…Although $5 medications is the most commonly used definition in the literature, 3,16 other cutoff values have been used, including 3, 6, 9, or 10 medications. 17 A better understanding of the relationships between polypharmacy/PIMs and physical function in this population could inform the development of interventions to optimize medication use in this population. For example, previous research has demonstrated that pharmacists play a significant role in assessing medication appropriateness, with respect to quality and safety of prescribing.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to survival, there was a significant correlation between the OS and PP in older advanced NSCLC patients. A recent metanalysis of the correlation between PP and survival outcomes for patients on chemotherapy across 11 prospective and retrospective studies [11] showed significant correlations only in 2 studies (1 on ovarian cancer [45] and the other on acute myeloid leukemia), [46] while the remaining 9 studies, including a study on patients taking oral imatinib for chronic myeloid leukemia [38], did not show any correlation between PP and mortality. Our data might suggest that prognostic significance differs according to cancer type and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have included only a small numbers of advanced lung cancer patients and have shown relatively high prevalence (7%-80%) of PP among the patients and its negative impact on clinical outcomes [11,16,[34][35][36][37]. However, the heterogeneity of patients' disease states, baseline characteristics, or treatment modalities across target populations or cancer types might impair the applicability of these results to different clinical situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation